Wannn Jersey and Sportwear / Muhammad Syamil Fikri Mohamad Paisal ... [et al.] - Mohamad Paisal, Muhammad Syamil Fikri; Sharif, Muhammad Zulsyahmi; Mohd Rasani, Nik Mohamad Irwan; Sakri, Nazrin Shazili (2022)
‘WANNN’ JERSEY AND SPORTSWEAR is a newly established jersey and sportswear boutique that will be operating in Pasir Mas, Kelantan. We have chosen ‘WANNN’ as our business official name; it symbolizes our target, which is we want to be the number one jerseys and sportswear seller in Kelantan. We will be selling jerseys with the latest design based on the latest session as our primary item. Then, sportswear such as shorts also will be offered to our customers. In the beginning, we may just offer jerseys and a few sportswear, but from time to time, we are targeted to offer most of the sportswear. With that, our boutique will be a one-stop centre for the customer to purchase any jerseys, sportswear, and sports equipment’s. We are choosing this industry to start our business because we realized the opportunity that our community is now involved in a healthy lifestyle. With that, they must look for suitable and comfortable attire to wear when they go jogging, playing football or hiking. We offer them high-quality jerseys and sportswear at affordable prices as well as exciting designs. Customers will also get extra benefits with us throughout the after-sales service we provide them. Apart from that, we are choosing this business because it is easier to conduct compared to the food services. It is because this business does not require a lot of raw materials and equipment to be run. Our business is run by the three main managers which are Marketing Manager, Operational Manager and Financial Manager whereas all of them under supervising of the one General Manager. We also will hire one administrative clerk to support the administration department and two operation staff to ensure our daily operations runs smoothly. To conclude, we hope that our proposed business will reach and achieve our vision to be the number customer’s number one choice centre in Kelantan to buy jerseys and sportswear. We are also hoping that in future, our ‘WANNN’ JERSEY AND SPORTSWEAR will be a famous sports boutique in Malaysia like Al-Ikhsan and Sports Direct.